Rat cardiomyocytes express a classical epithelial beta-defensin - Linde, Annika; Lushington, Gerald H.; Blecha, Frank; Melgarejo, Tonatiuh (My University, 2013)
Beta-defensins (BDs) are classical epithelial antimicrobial peptides of immediate importance in innate host defense. Since recent studies have suggested that certain BDs are also expressed in non-traditional tissues, including whole heart homogenate and because effector molecules of innate immunity and inflammation can influence the development of certain cardiovascular disease processes, we hypothesized that BDs are produced by cardiomyocytes as a local measure of cardioprotection against danger signals. Here we report that at least one rat beta-defensin, rBD1, is expressed constitutively in cardiomyocytes specifically isolated using position-ablation-laser-microdissection (P.A.L.M. Microlaser Technologies). RT-PCR analysis showed expression of a single 318 bp transcript in adult rat heart (laser-excised cardiomyocytes) and H9c2 cells (neonatal rat heart myoblasts). Moreover, the full length cDNA of rBD1 was established and translated into a putative peptide with 69 amino acid residues. The predicted amino acid sequence of the adult rat cardiac BD-1 peptide displayed 99% identity with the previously reported renal rBD1 and 88, 53, 53 and 50% identity with mouse, human, gorilla and rhesus monkey BD1 respectively. Furthermore, structural analysis of the cardiac rBD1 showed the classical six-cysteine conserved motif of the BD family with an alpha-helix and three beta-sheets. Additionally, rBD1 displayed a significantly greater number of amphoteric residues than any of the human analogs, indicating a strong pH functional dependence in the rat. We suggest that rBD1, which was initially believed to be a specific epithelium-derived peptide, may be also involved in local cardiac innate immune defense mechanisms.
Keywords: Innate immunity; Host defense peptides; Heart; Microdissection